Optimization Of The Managemenr In Maluku Health Analysis Department - Ramdhani M Natsir (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Introduction. Exam management is crucial in the implementation of evaluation in educational institutions. This is because the test implementation process is one of the determinants of the quality of an institution. This study aims to assess the optimization of examination management in the health analyst department of the Health Polytechnic of the Ministry of Health in Maluku. Methods. This study used a descriptive research design. This research was conducted in the health analyst department of the Maluku Health Polytechnic Ministry of Health in July - August 2019. The sample in this study were all employees and students in the Maluku Health Poltekkes Department of Health analyst with the sampling technique using total sampling. A Likert scale questionnaire was used as an instrument in the study. Results. There are respondents with more job distribution, namely 45 students (80.4%). Respondents who rated the application and website development category as very satisfied were 30 respondents (53.5%), and satisfied were 26 respondents (46.5%). Respondents who assessed the optimal management of the examination category were very satisfied with 38 respondents (67.8%), and satisfied with 18 respondents (32.2%). Conclusion. There is no relationship between the implementation of the SOP for exam management with optimal exam management, and there is a relationship between making applications and websites with optimal exam management.